Evaluasi Penyajian Laporan Keuangan Daerah Berdasarkan Standar Akuntansi Pemerintahan di Dinas Pekerjaan Umum dan Penataan Ruang Kota Manado - Sumanti, Alva Oktavianus; Sondakh, Jullie J.; Kapojos, Peter M. (Universitas Sam Ratulangi, 2022)
ABSTRACTGovernment Accounting Standards are accounting principles applied in preparing and presenting government financial reports, both central and regional. Statement of Financial Statement Presentation aims to regulate the presentation of(general purpose financial statementsgeneral purpose financial statements) in order to increase the comparability of financial statements both against budgets, between periods, and between entities. To achieve these objectives, this standard establishes all considerations in the context of the presentation of financial statements, guidelines for the structure of financial statements, and minimum requirements for the content of financial statements. The analytical method used is a qualitative method where the data collected is then classified and analyzed so that conclusions can be drawn. The results showed that the presentation of financial statements at the Manado City Public Works and Spatial Planning Office for the 2017-2018 fiscal year was in accordance with Government Regulation no. 71 of 2010 concerning Government Accounting Standards. The Manado City Public Works and Spatial Planning Office has presented 4 financial reports, namely the Budget Realization Report, Balance Sheet, Operational Report, and Notes to Financial Statements.Keywords: financial reports, budget realization reports, balance sheets, operational reports, notes to financial statements, accounting standards.